Analisis Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual Dalam Penyajian Laporan Keuangan Pada Pemerintahan Kota Medan - Anisa, Priendly; Sijabat, Jadongan; Br Siringoringo, Magdalena Judika (Jurnal Media Informatika, 2024)
The problem with the Medan City Government is obtaining a reasonable opinion with the exception of the North Sumatera Representative Audit Agency which is caused by a lack of compentent human resources in understanding accrual based SAP PP No.71 of 2010 in preparing Regional Government Financial Report (LKPD). This research aims to determine and analyze whether the implementation of accrual based SAP is in accordance with PP No.71 of 2010 and how efforts have been made to face the challenges of implementing Accrual Based SAP PP No.71 of 2010 to create a quality government system (good government). The type of research used is descriptive qualitative, by analyzing how Accrual Based SAP is implementing in presenting financial reports and how efforts are made to face the challenges of implementing Accrual Based SAP PP No.71 of 2010. The data obtained is primary data, obtained directly from the results of researchers interview with informants. The results of the research show that the Financial Reports of the Medan City Government have complied with the provisions stated in PP No.71 of 2010 and the Medan City Government is able to overcome challenges in implementing Accrual Based SAP and the efforts made can help improve the effectiveness of human resource performance in implementing Government Based Accounting Standards Accrual.